1988
DOI: 10.1128/jcm.26.9.1783-1786.1988
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of enteric adenoviruses among children in Thailand and the significance of these viruses in gastroenteritis

Abstract: In countries with temperate climates, enteric adenoviruses have been shown to be a substantial cause of pediatric gastroenteritis. To determine the incidence of àdenovirus infection in a tropical climate, stools were collected from children under age 7 during a 1-year period at an outpatient clinic in Bangkok, Thailand. Stools from 1,114 children with gastroenteritis and from 947 children without gastroenteritis were tested. Each stool was tested for adenovirus group antigen and for specific enteric adenovirus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
14
1
1

Year Published

1994
1994
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 15 publications
(7 reference statements)
4
14
1
1
Order By: Relevance
“…This finding suggested that about 4.4% of acute gastroenteritis in infants and children in Japan, Korea and Vietnam was due to adenovirus and 95.6% caused by other etiologic agents. This result was consistent with previously published reports worldwide and confirmed adenovirus as one of the important etiological agents for acute gastroenteritis among infants and children (13,14). Among all children with acute gastroenteritis, 88.9% were aged less than 36 months.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding suggested that about 4.4% of acute gastroenteritis in infants and children in Japan, Korea and Vietnam was due to adenovirus and 95.6% caused by other etiologic agents. This result was consistent with previously published reports worldwide and confirmed adenovirus as one of the important etiological agents for acute gastroenteritis among infants and children (13,14). Among all children with acute gastroenteritis, 88.9% were aged less than 36 months.…”
Section: Discussionsupporting
confidence: 93%
“…Among six subgenera, subgenus F adenoviruses were the most important etiologic agents of severe acute gastroenteritis, accounting for 1 to 20% of cases. They had a global distribution and were of comparable prevalence both in outpatients and hospitalized children in developed and developing countries (14,18,21,25).…”
mentioning
confidence: 99%
“…Enteric adenoviruses types 40141 were detected by Adenoclone EIA in 4.5% of the patients with diarrhea and in one child in the control group (1.3%). Similar detection rates have been reported by others [Kidd et al, 1986;Herrmann et al, 1988;Shinozaki et al, 1988;Jarecki-Khan et al, 1993;de Jong et al, 1993;Leite et al, 1985;Niel et al, 1986;Mistchenko et al, 19921. The etiological relationship of adenovirus and diarrhea was supported by the exclusion of other causative microorganisms and toxins [Stewien et al, 19931 except in one case with dual infection with astrovirus and especially for the enteric adenoviruses (Ad 40141) by significant difference in detection rates in diarrhea and in the controls.…”
Section: Discussionsupporting
confidence: 91%
“…In the few studies that have examined the role of EAs in an adult population, they appear to be less important causes of gastroenteritis than in children. No seasonality of EA infections was apparent in studies in temperate 31,[71][72][73] or tropical countries, 68,74 but few studies have reviewed multiple seasons.…”
Section: Epidemiologymentioning
confidence: 99%